THE CONSTRUCTION OF POSTCOLONIAL DISCOURSE IN THE STORY ROBOHNYA SURAU KAMI BY A. A. NAVIS - Resneri Daulay; Tomi Arianto (Asosiasi dosen IDEBAHASA KEPRI, 2020)
The story of Robohnya Surau Kami by A. A. Navis is an indirectly provocative work of fiction which arouse eastern society, represented in the life of Minangkabau people at that time, to realize their helplessness in order to take the initiative and express their silenced voices. This short story directs people to carry out a reformist movement in their constraints to the traditions they have lived for centuries because of colonialism. This short story was made in the 1990s where many Minangkabau Ulemas tended to focus more on education and intellectual activity rather than physical resistance. Orientalist discourse manifests itself as an influential system of ideas or as a network of various intellectual interests and meanings that are implied in various contextual, social, political, and constitutional of colonial hegemony. As alluded above, surau becomes a symbol of the institutions used by the colonial to facilitate the process of inculcating ideology and religion as the means of control in society. The result of this research represented that the construction of postcolonial discourse in the story Robohnya Surau Kami by AA. Navis reflected into the concept of demonization, dehumanization, western hegemonic. Paradigms that places eastern culture as old-fashioned, backward and stupidity are a construction to build demonization in the story. Thus, through the character of Ajo Sidi as an agent, the eastern people represented by the grandfathers are alienated, instigated, and subsequently experience a divided identity called by dehumanization. This demonization and dehumanization continued to be created and maintained by instilling hegemonic doctrines even without violence.